Colorectal cancer screening interventions in 2 health care systems serving disadvantaged populations: Screening uptake and cost‐effectiveness. Issue 21 (25th October 2018) - Lara, Christen L.; Means, Kelly L.; Morwood, Krystal D.; Lighthall, Westley R.; Hoover, Sonja; Tangka, Florence K.L.; French, Cynthia; Gayle, Krystal D.; DeGroff, Amy; Subramanian, Sujha
Abstract: Background: The objectives of the current study were to assess changes in colorectal cancer (CRC) screening uptake and the cost‐effectiveness of implementing multiple evidence‐based interventions (EBIs). EBIs were implemented at 2 federally qualified health centers that participated in the Colorado Department of Public Health and Environment's Clinic Quality Improvement for Population Health initiative. Methods: Interventions included patient and provider reminder systems (health system 1), provider assessment and feedback (health systems 1 and 2), and numerous support activities (health systems 1 and 2). The authors evaluated health system 1 from July 2013 to June 2015 and health system 2 from July 2014 to June 2017. Evaluation measures included annual CRC screening uptake, EBIs implemented, funds received and expended by each health system to implement EBIs, and intervention costs to the Colorado Department of Public Health and Environment and health systems. Results: CRC screening uptake increased by 18 percentage points in health system 1 and 10 percentage points in health system 2. The improvements in CRC screening uptake, not including the cost of the screening tests, were obtained at an added cost ranging from $24 to $29 per person screened. Conclusions: In both health systems, the multicomponent interventions implemented likely resulted in improvements in CRC screening. The results suggest that significant increases in CRC screening uptake can be achieved in federally qualified health centers when appropriate technical support and health system commitment are present. The cost estimates of the multicomponent interventions suggest that these interventions and support activities can be implemented in a cost‐effective manner. Abstract : The burden from colorectal cancer (CRC) could be reduced if substantially more individuals aged 50 years to 75 years were screened for CRC as recommended. This project demonstrated a successful partnership between the Colorado Department of Public Health and Environment and 2 health systems serving disadvantaged populations to successfully increase the uptake of CRC screening by 10% to 18% over 2 to 3 years at an added cost ranging from $24 to $29 per person screened.